ODR as a new way of resolving online disputes in E-commerce - Shukhrat Nuralievich Ruzinazarov; Mokhinur Bakhramova Bakhramovna (Genius Publishing Group, 2022)
In this article, we will discuss whether arbitrations based entirely on artificial intelligence are technologically feasible, that they perform the same functions as human arbitrators, and should be permitted by law. There is nothing in the concept of arbitration that requires human control, administration, or even access. In addition, we note that the existing legal framework for international commercial arbitration, in particular the New York Convention (NYC), is capable of adapting and adapting to fully artificial intelligencebased arbitration. We expect significant regulatory competition between jurisdictions to promote technology-assisted or even fully artificial intelligence-based arbitration, and emphasize that this competition will be beneficial. In this competition, we expect common law jurisdictions to have an advantage - machine learning applications for making legal decisions can be more easily developed for bottom-up thinking jurisdictions, where case law plays a crucial role
Keywords: Future professional activity; modeling; engineer; designer